Implementation of Stunting Prevention Policies in Rote Ndao Regency: A Phenomenological Study - William Djani; Jeny J. Therikh; Belandina Liliana Long; Apris A. Adu (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: This study investigates how stunting prevention policies are implemented in Rote Ndao Regency, Indonesia—a rural district where 1 in 5 children remains stunted despite recent gains. Methods: The research adopted a qualitative phenomenological single case design, drawing on semi structured interviews (n=12), non participant observations, and document review. Guided by implementation theory, the analysis centred on four variables—communication, resources, disposition, and bureaucratic structure—and followed data saturation principles. Results: Stunting prevalence declined from 22.4% (August?2022) to 21.7% (February 2023) in tandem with a 27% rise in the district health budget (IDR 118 billion IDR 150.7 billion, 2018 2022). Yet implementation remains hampered by human resource imbalances, limited community health worker training, and weak inter sectoral coordination. Conclusion: Despite these constraints, the commitment of midwives and Posyandu cadres has yielded modest but measurable progress. To sustain gains, we recommend integrated monitoring dashboards, evidence based HR redistribution, and structured community communication packages that embed policy convergence, robust M&E, and deep community participation—cornerstones of cohesive, adaptive, and sustainable rural health governance.